2023
DOI: 10.3389/fpls.2023.1159625
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of Limonium tetragonum to NaCl concentrations in hydroponic solution

Abstract: IntroductionLimonium (L.) tetragonum (Thunb.) A. A. Bullock, a halophyte that grows all over the southwest coast of Korea, is a medicinal plant with various pharmacological effects. The salt defense mechanism stimulates the biosynthesis of various secondary metabolites and improves functional substances. In this study, we investigated the optimal NaCl concentration for the growth and enhancement of secondary metabolites in hydroponically grown L. tetragonum.MethodsThe seedlings grown for 3 weeks in a hydroponi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Feng et al [14] compared two types of forage grasses and found that salt stress increased the dry matter content of forage grasses. Jang et al [15] found that the secondary metabolites of L. tetragonum were optimal at 75 mmol•L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al [14] compared two types of forage grasses and found that salt stress increased the dry matter content of forage grasses. Jang et al [15] found that the secondary metabolites of L. tetragonum were optimal at 75 mmol•L −1 .…”
Section: Introductionmentioning
confidence: 99%